The Systems View of Life: A Unifying Conception of Mind, Matter, and Life - Capra, Fritjof (Cosmos and History: The Journal of Natural and Social Philosophy, 2015)
<!–[if gte mso 9]> <![endif]–>Over the last thirty years, a new systemic understanding of life has emerged at the forefront of science. It integrates four dimensions of life: the biological, the cognitive, the social, and the ecological dimension. At the core of this new understanding we find a fundamental change of metaphors: from seeing the world as a machine to understanding it as a network. One of the most radical philosophical implications of the systems view of life is a new conception of mind and consciousness which, for the first time, overcomes the Cartesian division between mind and matter. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> 800x600 <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-AU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>